PECULIARITIES OF SPEECH CULTURE IN BUSINESS COMMUNICATION - Tsaryk, Olga; Panychok, Tetiana; Maksymchuk, Zhanna (Mountain School of Ukrainian Carpaty, 2023)
This article focuses on the importance of language culture in the context of business communication. In today's world, business communication has become an integral part of the successful operation of any organization. It includes information exchange, negotiations, presentations, and communication with clients and colleagues, making language culture a crucial aspect of its effectiveness. The authors examine the key aspects of language culture in the business environment and its impact on communication outcomes in organizations, emphasizing the importance of proper language usage, expressiveness, speech structure, and other essential elements of language culture for achieving business communication goals. Special attention is given to the intercultural aspects of business communication since many companies in the modern world have international connections and interact with clients and partners from different countries and cultures. The article analyzes the challenges associated with differences in cultural norms and communication requirements and provides recommendations for effective communication in intercultural contexts. The impact of modern information technologies on language culture in business communication is also discussed. Communication through email, video conferences, social networks, and other tools has undergone significant changes in recent years, and this has a significant influence on how language is used in the business environment. The article calls for the development of language culture skills as an essential aspect of professional development. It provides readers with practical advice and tools for improving their communication skills in business and underscores the importance of continuous self-improvement in this aspect. In conclusion, the authors offer a deep analysis and important insights into the role of language culture in the modern business environment and provide valuable recommendations for enhancing the quality of business communication.